Incidencia de la cartera vencida en la liquidez de la caja solidaria de ahorro y credito "wiñari", ubicada en el Cantón Latacunga, Provincia Cotopaxi de los años 2016 - 2017 - Chiliquinga Taipe, Carmen Ramona (2018)
The research project presents information regarding to the incidence of the overdue portfolio on financial liquidity in order to establish the reality of the problems that caused the default of the credit obligations by the partners, the analysis of the overdue portfolio in the cash solidary box of Savings and Credit "Wiñari" company of the years 2016 – 2017, the same one which allowed to know the problems of the financial institution, among them the delinquency of the borrowers that induced the expiration of the credits that affected the liquidity of this financial institution due to some factors, causing delays in the payment of credits granted among the main causes that influenced, are derived from economic and labor instability, nonconformity of remuneration, inadequate control of personal income, natural disasters and others. For the development of the project it was necessary to apply methods, techniques and research instruments that allowed stipulating the causes of non-compliance of the partners. The importance of the project was based on the research and the financial analysis carried out, allowing to investigate the effect of the overdue portfolio on the liquidity of the aforementioned years, thus reaching the objectives and goals set for the development of the research. In this way generating an economic, social and technical impact towards the direct beneficiaries of the project, linking in a general way the "Wiñari" Solidarity Savings and Credit Company and the indirect beneficiaries the inhabitants in the San José de Poalo Parish, other financial institutions with similar services and the student who did the research.